Studi Literatur Gambaran Klinis Dan Pengobatan Sapi Bali (Bos sondaicus) Yang Terinfestasi Thelazia spp. - Sabneno, Jemris; Simarmata, Yohanes T R M R; Utami, Tri (Jurnal Veteriner Nusantara, 2024)
Thelaziasis is a parasitic disease that was difficult to controlled by farmers. This disease is caused by parasitic worms from the nematode class Thelazia spp. which infested the eyes of bali cattle. The vector that causes Thelaziasis in cattle is Musca spp. Larvae and adult worms of Thelazia spp. live in the conjunctival sac and tear ducts of bali cattle. Thelaziasis in cattle was caused by Thelazia rhodesii, Thelazia gulosa and Thelazia skrjabini. The purpose of this study is to determine the clinical manifestation, diagnosis and treatment of bali cattle infested with Thelazia spp. and its prevalence in several regions in Indonesia. The method used was a qualitative descriptive method with a literature study approach. Based on the results of the study, it was known that bali cattle infested with Thelazia spp. has a glossy/dull coat and showing symptoms like stress, anorexia, with severe conjunctivitis, and swelling of the conjunctiva while clinical signs such as body temperature, pulsus and respiration are normal. Bali cattle infested by Thelazia spp. exhibited same clinical symptoms, like lacrimation and conjunctivitis to keratitis, epiphora, edema of the eyelids, corneal ulcers, and blindness. Diagnosis of Bali cattle infested with Thelazia spp. based on the discovered of the Thelazia spp. on the conjunctival sac of both eyelids and further examination can be done with an electron microscope to determine the morphology of the Thelazia spp. species. Treatment of thelaziasis disease can be done with commercial drugs such as Tetramisole 15mg/kg body weight, Levamisole 5g/kg body weight, and Ivermectin 0.2 to 0.5 mg/kg body weight and herbal ingredients such as 3 to 5 drops of betel leaf boiled water in the eyes of bali cattle infested by Thelzazia spp. The prevalence of Thelaziasis in Indonesia was strongly influenced by fly vectors and the management of bali cattle production.